An Analysis of Universality in Khalil Gibran’s The Prophet - Faiz Muhammad Brohi; Ahmed Ali Brohi; Nasarullah Kabooro (Linguistics and Literature Review, 2021)
This research article portrays the comprehensive picture of a society in which Khalil Gibran is found giving numerous principles aimed at the prevalence of harmony and peace. His book (The Prophet) is comprised of twenty-six different essays that lead towards a perfect society. Gibran’s art of depicting Universality in The Prophet inspires people towards the creation of an ideal society. The themes of the book, which are universal, are not only concerned with one nation but with all nations and religions across the globe. This study highlights the issues of people along with solid solutions through given essays. The study explores, discusses, and critically analyzes multiple socio-psychological issues facing men in his/ her brief sojourn on the planet earth. The study exploits qualitative design using textual analysis based on the novel's close reading to arrive at results.Keywords: Harmony and peace, inspirational and motivational thoughts.